1984
DOI: 10.2307/1919153
|View full text |Cite
|
Sign up to set email alerts
|

The Indians' New World: The Catawba Experience

Abstract: August i6o8 John Smith and his band of explorers captured an Indian named Amoroleck during a skirmish along the Rappahannock River. Asked why his men-a hunting party from towns upstreamhad attacked the English, Amoroleck replied that they had heard the strangers "were a people come from under the world, to take their world from them."1 Smith's prisoner grasped a simple yet important truth that students of colonial America have overlooked: after I492 native Americans lived in a world every bit as new as that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Para nos afastarmos da atitude de que o uso dos documentos é um exercício literal apenas para a obtenção de informações intencionalmente criadas por aqueles que os registraram, necessitamos abordá-lo como um corpo de textos (da mesma forma como os antropólogos e folcloristas fazem com os contos, mitos, etc.) e estar atentos para o fato envolvendo a interação entre indígenas americanos e europeus faça excelente uso de documentos e evidências materiais de forma combinada, visando a examinar não apenas resistência, mas também construções intencionais de identidade cultural pelos indígenas (e.g., Bradley, 1987;Bragdon, 1988;Brenner, 1988;Crosby, 1988;Hamell, 1983Hamell, , 1987Merrell, 1988Merrell, , 1989. 18 Talvez o clamor para permanecer um pré-historiador diante da evidência textual derive do que parece ser uma preocupação subjacente de que, acrescentando os documentos a essa equação, se adote uma abordagem crítica não realmente necessária, uma vez que a evidência material é, de certo modo, mais direta que os textos e, portanto, mais confiável, necessitando menos análises críticas.…”
Section: Dos Artefatos Da Hegemonia Aos Artefatos No Discurso Hegemônicounclassified
“…Para nos afastarmos da atitude de que o uso dos documentos é um exercício literal apenas para a obtenção de informações intencionalmente criadas por aqueles que os registraram, necessitamos abordá-lo como um corpo de textos (da mesma forma como os antropólogos e folcloristas fazem com os contos, mitos, etc.) e estar atentos para o fato envolvendo a interação entre indígenas americanos e europeus faça excelente uso de documentos e evidências materiais de forma combinada, visando a examinar não apenas resistência, mas também construções intencionais de identidade cultural pelos indígenas (e.g., Bradley, 1987;Bragdon, 1988;Brenner, 1988;Crosby, 1988;Hamell, 1983Hamell, , 1987Merrell, 1988Merrell, , 1989. 18 Talvez o clamor para permanecer um pré-historiador diante da evidência textual derive do que parece ser uma preocupação subjacente de que, acrescentando os documentos a essa equação, se adote uma abordagem crítica não realmente necessária, uma vez que a evidência material é, de certo modo, mais direta que os textos e, portanto, mais confiável, necessitando menos análises críticas.…”
Section: Dos Artefatos Da Hegemonia Aos Artefatos No Discurso Hegemônicounclassified
“…Through time "Kadapau" (Catawba), the name of the northernmost town mentioned by Lawson, became the name commonly used for all the people of the valley, and this core of people together with the dispossessed 186 people of other tribes began to be known to the British colonies as the Catawba Nation. Thus, during the early 1700s the Catawba Nation became more than the descendants of the inhabitants of the Catawba River Valley and the older chiefdom of Cofitacheque; it became a nation comprised of a variety of aboriginal people from all over the southeastern portion of North America Historian James H. Merrell has recently discussed the "Catawba Experience" in the 18th century and has pointed out that (Merrell 1984a: 548) In addition to the core of people mentioned by Lawson -the Kadapaus, Wisacks, Sugerees, and Esaws -a list of peoples who came to reside in the Catawba Nation during the 18th century includes (Baker 1975;Merrell 1984a) the Waterees, Congarees, Santees, Saponis, Cussoes, Cheraws, Peedees, Yamassees, Coosas, Enos, Occaneeches, Keyauwees, Chowans, and Nachees! Moreover, in another paper entitled "The Racial Education of the Catawba Indians," Merrell (1984b) has demonstrated that relationships between blacks and the people who made up the Nation were more cordial in the early part of the 18th century than at any time thereafter.…”
Section: The Catawba Nationmentioning
confidence: 99%